2012
DOI: 10.1109/tmi.2011.2167628
|View full text |Cite
|
Sign up to set email alerts
|

NMF-SVM Based CAD Tool Applied to Functional Brain Images for the Diagnosis of Alzheimer's Disease

Abstract: This paper presents a novel computer-aided diagnosis (CAD) technique for the early diagnosis of the Alzheimer's disease (AD) based on nonnegative matrix factorization (NMF) and support vector machines (SVM) with bounds of confidence. The CAD tool is designed for the study and classification of functional brain images. For this purpose, two different brain image databases are selected: a single photon emission computed tomography (SPECT) database and positron emission tomography (PET) images, both of them conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 42 publications
0
84
0
Order By: Relevance
“…The use of SVM in neuroimaging research has been reported in multiple (Cuingnet, Chupin, Benali, & Colliot, 2010; Cuingnet et al., 2011; Kloppel et al., 2008; Magnin et al., 2009; Padilla et al., 2012; Tanoori, Azimifar, Shakibafar, & Katebi, 2011; Zhang, Shen, & Alzheimer's Disease Neuroimaging Initiative, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The use of SVM in neuroimaging research has been reported in multiple (Cuingnet, Chupin, Benali, & Colliot, 2010; Cuingnet et al., 2011; Kloppel et al., 2008; Magnin et al., 2009; Padilla et al., 2012; Tanoori, Azimifar, Shakibafar, & Katebi, 2011; Zhang, Shen, & Alzheimer's Disease Neuroimaging Initiative, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…As previously stated CAD is a general tool used for a variety of application such as to diagnose the disease in medical applications. CAD helps the physicians, researchers in diagnosing the disease in less time by identifying he patterns, making fewer efforts [11].…”
Section: Neuroimaging and Radiology In Diagnosis Of Alzheimer Diseasementioning
confidence: 99%
“…It is suitable for high dimensional classification problems, where not too many examples exist. SVM has been utilized, for instance, in [8] for classifying MR images and in [9], [10] to classify Position Emission Tomography (PET) images. All these works used voxel intensity (VI) as features.…”
Section: Introductionmentioning
confidence: 99%